2017
DOI: 10.1007/s11682-017-9732-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of longitudinal white matter degeneration and cerebrospinal fluid biomarkers of neurodegeneration, inflammation and Alzheimer’s disease in late-middle-aged adults

Abstract: Alzheimer’s disease (AD) is characterized by substantial neurodegeneration, including both cortical atrophy and loss of underlying white matter fiber tracts. Understanding longitudinal alterations to white matter may provide new insights into trajectories of brain change in both healthy aging and AD, and fluid biomarkers may be particularly useful in this effort. To examine this, 151 late-middle-aged participants enriched with risk for AD with at least one lumbar puncture and two diffusion tensor imaging (DTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 76 publications
(85 reference statements)
7
32
1
Order By: Relevance
“…YKL-40 was quantified using sandwich ELISAs (R&D Systems, Minneapolis, Minn., USA). CSF assays were performed in two batches and corrected for batch differences as previously described 69 , 70 . For correlational statistical analysis, we used the “cor.test” function in R to calculate Spearman’s rank correlation coefficients between CSF biomarker levels and normalized relative abundances for the 13 differentially abundant genera.…”
Section: Methodsmentioning
confidence: 99%
“…YKL-40 was quantified using sandwich ELISAs (R&D Systems, Minneapolis, Minn., USA). CSF assays were performed in two batches and corrected for batch differences as previously described 69 , 70 . For correlational statistical analysis, we used the “cor.test” function in R to calculate Spearman’s rank correlation coefficients between CSF biomarker levels and normalized relative abundances for the 13 differentially abundant genera.…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion weighted imaging data were preprocessed using a robust pipeline also used in a number of previous studies (Adluru et al, 2014; Ly et al, 2016; Merluzzi et al, 2016; Racine et al, 2017). DWI data from baseline and follow-up visits were first converted from Digital Imaging and Communication in Medicine (DICOM) format to Neuroimaging Informatics Technology Initiative (NIFTI) format and visually inspected for artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…Age-related trajectories of white matter macro-and microstructure typically reflect increases in anisotropy and decreases in diffusivity during childhood, adolescence and early adulthood (Krogsrud et al, 2016;Tamnes et al, 2018;Westlye et al, 2010), and subsequent anisotropy decreases and diffusivity increase in adulthood and senescence (Cox et al, 2016;Davis et al, 2009). While the field has primarily been dominated by cross-sectional studies, which by design lack information on individual trajectories (Schaie, 2005), longitudinal studies in the last decade have shown corresponding white matter changes in both development and ageing (Barrick et al, 2010;Bender et al, 2016;Bender & Raz, 2015;de Groot et al, 2016;Likitjaroen et al, 2012;Racine et al, 2019;Sexton et al, 2014;Storsve et al, 2016;Teipel et al, 2010). However, studies that have evaluated individual differences in change across a wide age range are rare (Bender et al, 2016).…”
Section: Introductionmentioning
confidence: 99%